A new kid on the block: Outcomes with Kcentra 1 year after approval. Issue 6 (December 2015) - Berndtson, Allison E.; Huang, Wan-Ting; Box, Kevin; Kobayashi, Leslie; Godat, Laura N.; Smith, Alan M.; Weingarten, David; Coimbra, Raul
Abstract : BACKGROUND: As the population ages, more trauma patients are admitted with coagulopathy. Fresh frozen plasma is effective in reversing coagulopathy caused by warfarin; however, it is not appropriate for all patients. Prothrombin complex concentrates (PCCs) are an alternative for patients who require emergent reversal, minimal-volume administration and who have a supratherapeutic international normalized ratio (INR). A four-factor PCC initially approved in Europe is now available in the United States. We sought to review our experience with Kcentra (4F-PCC) in the first year following Food and Drug Administration approval. METHODS: All trauma patients admitted to an academic Level 1 trauma center between July 15, 2013, and July 15, 2014, who received 4F-PCC for reversal of warfarin-induced coagulopathy were reviewed. 4F-PCC was given as per protocol. Univariate analysis was performed to examine patient demographics, injury characteristics, coagulation studies, 4F-PCC dose, vitamin K use, transfusions, response to reversal, duration of reversal, complications, and mortality. RESULTS: Twenty-six patients met study criteria. Of these patients, 34.6% were reversed because of intracranial hemorrhage. The mean INR decreased from 5.7 ± 6.1 (range, 1.6–30) to 1.5 ± 0.4 (range, 1.2–2.6) after 4F-PCC administration. One patient (3.8%) received concurrent fresh frozen plasma. For patients with an initial INR greater than 5.0, the mean INR decreased from 12.0 ± 8.2 to 1.6 ± 0.5. Forty-eight hours following 4F-PCC administration, mean INR for all patients remained 1.4 ± 0.4 (range, 1.0–2.6). Of the patients, 80.8% received vitamin K over this period. Fourteen patients had a pre–4F-PCC thromboelastogram; four were hypocoagulable. Two patients had repeat thromboelastograms after 4F-PCC was given, which demonstrated normal coagulation. Of the patients with intracranial hemorrhage, 66.7% showed radiographic progression of the initial insult on post–4F-PCC head computed tomography, while only 11.1% progressed clinically. In-hospital mortality was 0%. There were no thromboembolic complications. CONCLUSION: 4F-PCC effectively reverses elevated INRs in trauma patients with warfarin-induced coagulopathy, with results lasting more than 48 hours after administration. LEVEL OF EVIDENCE: Therapeutic study, level V.